Immunological context of brain injury - N. G. Plekhova (SPb RAACI, 2021)
The parameters of several populations of immune cells (T cell populations, macrophage subpopulations) in peripheral blood and brain were studied in a clinically significant model of mild traumatic brain injury among rats. The population of resident cells of innate immunity of microglia and brain astrocytes with local tissue damage is involved in the implementation of the inflammatory response, it is also shown that in case of trauma, blood leukocytes can overcome the blood-brain barrier and penetrate the brain parenchyma. The methods of flow cytometry and immunofluorescence were used. An increase in the number of monocytes and neutrophils up to 1 day, after a mild traumatic brain injury (TBI) with a subsequent decrease to the end of the observation period was noticed. It was determined, that the number of CD45+ cells, CD3+T cells decreased at 1 days post-injury (dpi), and rose slightly by 14 dpi, the percentage of CD4+T cells continuously declined from 7 to 14 dpi, while the percentage of CD8+T cells increased from 7 to 14 dpi. With mild traumatic brain injury in animals, a significant (3-10 times) decrease in the number of microvessels with a positive reaction to the presence of SMI 71 on the 8th and 14th day after head injury was observed. Intensive staining of SMI 71 microvessels was sometimes observed with an increase in the area of a positive reaction. Thin positive deposits of the reaction product are observed in the brain of healthy animals around the wall of the microvessel. In the damaged brain, CD45high/CD11b+ positive macrophages of the M1 subpopulation appeared in the brain tissue on the 2nd day after TBI and a significant amount was observed on the 8-14th day. In the corpus callosum and ipsilateral region of the striatum, the content of cells expressing CD16/11b+ reached a maximum 8 days after TBI, which correlated with a decrease in the positive response to the presence of endothelial antigen SMI 71. Thus, in the acute period of mild TBI, the presence of neuroimmunopathological processes is determined in the brain, which can subsequently result to the dysregulation of neuroimmune connections.